Participation in higher education: a random parameter logit approach with policy simulations - Darragh Flannery; Cathal O'Donoghue (Institute for the Study of Labor (IZA), 2009)
In this paper we present a theoretical model of higher education participation. We assume that young people that complete upper secondary education are faced with three choices, go to higher education, not go to higher education or go to higher education and work part time. Utilizing the Living in Ireland survey data 1994-2001 we model this choice in an Irish context by variation in costs (direct and indirect), the estimated lifecycle returns and household credit constraints. Using a random parameters logit choice model we find that simulated lifecycle earnings positively impact the educational/labour choices of young individuals in Ireland. This positive relationship is also found to be true for a choice-specific household income variable constructed in the paper. From the random parameters logit estimations we also find that preferences for choices with higher simulated lifecycle earnings and household income vary across individuals. We conduct policy simulations from our estimations and found that increasing student financial aid levels by 10% combined with a slight widening of the income limits for these aids can lead to significant movement away from the decision to not enter higher education.
urn:nbn:de:101:1-20090605206
Keywords: I23; C35; 330; Higher education participation; random parameters logit model; lifecycle simulated earnings; higher education policy; Studium; Bildungsverhalten; Lebenseinkommen; Bildungsertrag; Verschuldungsrestriktion; Logit-Modell; Irland